Current State of Neuromodulation for Constipation and Fecal Incontinence in Children: A Systematic Review - Iacona, Roberta; Ramage, Lisa; Malakounides, Georgina (European Journal of Pediatric Surgery, 2019)
Background Neuromodulation is the application of electrical stimulation on nerve fibers to modulate the neuronal activity. Its use for chronic constipation and fecal incontinence has increased in popularity over the past few years. Invasive and noninvasive techniques are currently available. We reviewed the current literature on the application of the neuromodulation techniques in the management of chronic constipation and fecal incontinence in children.Materials and Methods A search of Healthcare Database Advanced Search, Embase, Medline, and Cochrane database was performed in accordance with PRISMA guideline. Terms used in the search included neuromodulation, nerve stimulation, fecal/fecal incontinence, incontinence, constipation, children, and pediatric/pediatric.Results Two-hundred forty-one papers were screened. Fourteen papers were included for the systematic review: seven were selected for the ISNM (implantable sacral nerve modulation) technique, one for the transcutaneous tibial nerve stimulation), one for the transcutaneous sacral nerve modulation), and five for the transcutaneous interferential sacral nerve stimulation. Results showed an overall improvement in constipation symptoms in 79 to 85.7% of patients, resolution of symptoms in 40%, reduced use of ACE stoma/transanal irrigation system in 12.5 to 38.4%, and improvement in incontinence symptoms in 75%. High complication rate was reported (17–50%) in the ISNM group. No complications were reported in the non-invasive group.Conclusion Neuromodulation is a promising tool in the management of constipation refractory to medical treatment and fecal incontinence in children. Noninvasive techniques provide good results with no complications. A longer term follow-up will provide more information regarding patient compliance and sustainability of benefits of these new techniques.
Keywords: neuromodulation; fecal incontinence; chronic constipation; pediatric